2022
DOI: 10.1093/beheco/arac011
|View full text |Cite
|
Sign up to set email alerts
|

What is cultural evolution anyway?

Abstract: The term cultural evolution has become popular in the evolutionary human sciences, but it is often unclear what is meant by it. This is generating confusion and misconceptions that are hindering progress in the field. These include the claim that behavioral ecology disregards culture. We argue that these misunderstandings are caused by the unhelpful use of term cultural evolution to identify both a phenomenon—culture changing through time—and a theory to explain it—the potential role of cultural transmission b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 13 publications
(12 reference statements)
0
26
0
Order By: Relevance
“…So inclusive fitness is still a framework that potentially has predictive power with respect to the design of cultural phenotypes. Behavioural ecology models have long been used to increase our understanding of the diversity of human behaviour, including cultural behaviour [ 42 ], and here we have shown that inclusive fitness interests appear to play a role in shaping both parental preferences and the design of a costly religious institution. Inclusive fitness can help us to make predictions about the phenotypes of cultural institutions that develop in human populations [ 42 ].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…So inclusive fitness is still a framework that potentially has predictive power with respect to the design of cultural phenotypes. Behavioural ecology models have long been used to increase our understanding of the diversity of human behaviour, including cultural behaviour [ 42 ], and here we have shown that inclusive fitness interests appear to play a role in shaping both parental preferences and the design of a costly religious institution. Inclusive fitness can help us to make predictions about the phenotypes of cultural institutions that develop in human populations [ 42 ].…”
Section: Discussionmentioning
confidence: 89%
“…So inclusive fitness is still a framework that potentially has predictive power with respect to the design of cultural phenotypes. Behavioural ecology models have long been used to increase our understanding of the diversity of human behaviour, including cultural behaviour [42], and royalsocietypublishing.org/journal/rspb Proc. R. Soc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is sometimes suggested that behavioural ecology is unfit for the study of behaviour in our species, because it downplays or completely disregards the role of cultural evolution. As we have argued elsewhere (Micheletti, Brandl and Mace 2022), we believe that this is a misconception that stems from the unhelpful use of the term "cultural evolution" to indicate both a phenomenon -culture changing through time -and a theory to explain it -the central role played by transmission biases in shaping culture and an associated focus on cultural inheritance. Ambiguity surrounding this term is widespread both in the literature and in informal discussion, and we may even have been guilty of this ourselves.…”
Section: Cultural Evolution: Clarifying the Confusion Between Phenome...mentioning
confidence: 95%
“…The latter could benefit, beyond the sophisticated analyses of big data mined from ethnographic work, from the integration with the intellectual legacy and practice of core anthropology and thus propitiate the synergistic interaction of disciplines. Attempts of rapprochement of disciplines from the natural sciences that lack pluralism and present a narrow view are deemed examples of 'Wilson's effect'.Social Media summary: Lévi-Strauss' anthropological work in its abstraction and modeling provides an example of the search for universals and big data analysisThe relatively new field of cultural evolution aims at understanding different aspects of human cumulative culture (Cavalli-Sforza & Feldman, 1981;Mesoudi, 2011;Antweiler, 2012;Lewens, 2015;Micheletti et al, 2022). The majority of studies of cultural evolution concern the processes that lead to cultural change within and among populations.…”
mentioning
confidence: 99%